(untitled) (Bangladesh Pharmaceutical Journal, 2016)
Spondias pinnata is a medicinal herb belonging to the family of Anacardiaceae. Locally it is known as Amra and has a history of ethno-medicinal properties. The crude ethanolic extract along with different partitionates of the leaves of S. pinnata were evaluated for their possible thrombolytic and membrane stabilizing activities. The activities of the leaf extract were evaluated by using standard drugs; streptokinase for thrombolytic and acetyl salicylic acid for anti-inflammatory activities. In this study, among all partitionates the ethyl acetate soluble fraction showed highest % of clot lysis (58.06%) as compared to (69.23%) and (3.03%) exhibited by the standard streptokinase and water. On the other hand, ethyl acetate soluble fractionates also significantly inhibits the haemolysis of human erythrocyte membrane both in induced by hypotonic solution (65.33 ± 0.50%) and by heat (56.22 ± 0.69%), respectively as compared to (75.92 ± 29%) and (71.12 ± 0.26%) demonstrated by acetyl salicylic acid. Our study revealed that satisfactory amount of flavonoid content (132.27 ± 0.25) showed a significant and positive correlation between total flavonoid content with thrombolytic and membrane stabilizing activities. Bangladesh Pharmaceutical Journal 19(1): 48-52, 2016